The solution is y = (5x - 9) / 3
To solve the equation 5x - 3y = 9 for y, we need to isolate the variable y on one side of the equation.
Step 1: Move the term with y to the other side of the equation.
Subtract 5x from both sides of the equation:
5x - 3y - 5x = 9 - 5x
This simplifies to:
-3y = 9 - 5x
Step 2: Divide both sides by -3 to solve for y:
y = (9 - 5x) / -3
Therefore, the solution for y is:
y = (-9 + 5x) / 3
You can also express the solution as:
y = (5x - 9) / 3
Either form represents the solution for y in terms of x for the given equation.
Learn more about Equations here:
brainly.com/question/10724260?
#SPJ6